ANALYSIS OF WEB BASED TOURISM INFORMATION SYSTEMS UTILIZATION (Case Study at Integrated Office Department of Culture and Tourism City of Malang) - Decca Putri Rahajeng (Jurnal Administrasi Bisnis, 2015)
The purpose of this study is to analyze and determine weaknesses and strengths of the use of web-based tourism information systems at the Department of Culture and Tourism of the city of Malang. This research was conducted by using descriptive method with qualitative research approach. The data collection was done by using interviews, observation and documentation. Data analysis was performed using data analysis spiral in accordance with the stages. The results showed that the use of web-based tourism information system which has been implemented by the Department of Culture and Tourism of the city of Malang is very effective in helping the agency to promote tourism in the city of Malang to the general public, domestic and foreign tourists. With the use of web-based tourism information system, tourists or visitors to the website can access the website of Culture and Tourism Malang for 24 hours anywhere and anytime. Keywords: information systems utilization, tourism information systems, web based tourism.